Aerodigestive dysbiosis in children with chronic cough. Issue 9 (8th July 2018) - Kazachkov, Mikhail; Kapoor, Bianca C.; Malecha, Patrick W.; Wu, Benjamin G.; Li, Yonghua; Levine, Jeremiah; Erkman, Jessica; Fitzgerald, Kathryn; Moy, Libia; Segal, Leopoldo N.
Abstract: In pediatric patients with chronic cough, respiratory culture techniques commonly yield negative results. Studies using culture‐independent methods have found a high relative abundance of oral microbes in the lower airways, suggesting that the topographical continuity, and dynamics of the intraluminal contents of the aerodigestive system likely influence the lower airway microbiota. We hypothesize that in subjects with chronic cough, clinical diagnosis will correlate with distinct microbial signatures detected using culture‐independent methods. Study Design and Methods: We enrolled 36 pediatric subjects with chronic cough in a cross‐sectional study. Subjects were categorized into four clinical groups: asthma, bacterial bronchitis, neurologically impaired‐orally fed, and neurologically impaired enterally fed. Samples from the aerodigestive tract were obtained through bronchoscopy and upper endoscopy. 16S rRNA gene sequencing compared the microbiota from bronchoalveolar lavage (BAL), tracheal, supraglottic, esophageal, gastric, and duodenal samples. Results: We observed that the lower airway microbiota of asthma subjects had higher α diversity as compared with the other groups. β diversity analysis of BAL samples revealed significant differences between the groups. Among the taxonomic differences found, most differentially enriched taxa were upper airway organisms such as Rothia, Gemellaceae (u.g. or uncharacterized genus), and Granulicatella in asthma, Prevotella in bacterial bronchitis, and Veillonella in neurologically impaired orally fed subjects. Greater dissimilarity between the upper airway and lower airway microbiota was associated with increased neutrophilic airway inflammation. Conclusions: Distinct dysbiotic signatures can be identified in the lower airway microbiota of pediatric subjects with chronic cough that relates to the degree and type of inflammation.